The role of sucrose in amino polymers synthesized by the strongly acid process - Nuno A. Costa (2013)
This article studies the incorporation of sucrose in amino polymers produced by the strongly acid process and its role on the physico-mechanical properties and aldehyde emission of the resulting particleboards. The incorporation of sucrose at different pH environments was studied and differences on molecular weight of resins were analyzed by gel permeation chromatography/size exclusion chromatography (GPC/SEC) and characteristic chemical bands by Raman spectroscopy. A reaction mechanism was proposed to explain the observed differences in GPC/SEC chromatograms and was supported by Raman spectra. It was observed that small amounts of sucrose incorporated in polymeric matrix are sufficient to improve the physico-mechanical properties of particleboards; the sucrose addition protocol plays a key role on these improvements.